A Digital Library Example in the Digital Age: İstanbul Bilgi University Library and e-Resources - Banu Elçi (Türk Kütüphaneciliği)
This article describes the ongoing of the traditional library and service concept alteration to the library and service concept of the digital age and refers to an instance as İstanbul Bilgi University Library and e-Resources that pioneers technological advances and digital applications to be integrated into the library field. In this sense it involves services, developments, applications and projects provided by Bilgi Libraries.This article also accounts for a number of works which integrated digital resources and applications and social network interactions of the internet and the web of the digital age and how they are adjusted to the library area.In this context, it refers to an evolvement of a different approach of libraries and enhacements diverged from customary and adopted library service concepts and reveals through the medium of samples from İstanbul Bilgi University Library and e-Resources.